2020
DOI: 10.1089/tmj.2020.0134
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Remote Monitoring for the COVID-19 Pandemic

Abstract: COVID-19 has created the need for population-level screening, and telemedicine is ideally positioned to enable this. As telemedicine has evolved over the last decade, remote monitoring emerged as a new and powerful modality. COVID-19 requires scaled interactions with populations in near real-time. Remote monitoring has specific operational and design features that are well suited for the COVID-19, especially the asynchronous communication. Monitoring can be used in particular to gather pandemic data and obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 5 publications
0
76
0
5
Order By: Relevance
“…It has been reported that telepsychiatry may be efficient to screen for mental health symptoms in COVID-19 patients and to optimize treatment 216 , or that online assessments are helpful prior to appointments and as follow-up 217 . Continued care is, thus, enabled in a time when the health care systems are overwhelmed 218 .…”
Section: Telemedicine During the Covid-19 Pandemicmentioning
confidence: 99%
“…It has been reported that telepsychiatry may be efficient to screen for mental health symptoms in COVID-19 patients and to optimize treatment 216 , or that online assessments are helpful prior to appointments and as follow-up 217 . Continued care is, thus, enabled in a time when the health care systems are overwhelmed 218 .…”
Section: Telemedicine During the Covid-19 Pandemicmentioning
confidence: 99%
“…RPM involves the asynchronous transmission of health care data between physically distant patients and health care providers to aid in clinical management 9,10 and it has been shown to be a viable alternative to traditional in-person care in terms of hospital readmission and symptom detection. 6,11,12 The value of using RPM to deliver care to patients during the COVID-19 pandemic was recently described, 13 as it is low-cost, scalable, and has bidirectional features, which foster communication between patients and health care providers in an environment devoid of contamination. 14 Moreover, RPM provides the opportunity for continuous clinical data collection from which future predictive models can be generated.…”
mentioning
confidence: 99%
“…During the public health emergency due to COVID-19 telemedicine has thrived and emerged worldwide as an indispensable resource to improve surveillance of patients, contain the spread of the disease, favor early identification and prompt management of infected people, but particularly to ensure continuity of care of vulnerable patients with multiple chronic diseases, including hypertension [2,3]. The recent pandemic has strongly promoted the use of remote monitoring and televisits, where in-person consulting has been greatly reduced or impossible [86,87].…”
Section: Disastersmentioning
confidence: 99%